2019
DOI: 10.3390/genes11010006
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis in Pancreatic Ductal Adenocarcinoma: Current Standing and Methodologies

Abstract: Pancreatic ductal adenocarcinoma is an extremely aggressive disease with a high metastatic potential. Most patients are diagnosed with metastatic disease, at which the five-year survival rate is only 3%. A better understanding of the mechanisms that drive metastasis is imperative for the development of better therapeutic interventions. Here, we take the reader through our current knowledge of the parameters that support metastatic progression in pancreatic ductal adenocarcinoma, and the experimental models tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 180 publications
0
43
0
1
Order By: Relevance
“…There are preferential sites for metastases from PDAC, such as liver, lungs, and peritoneum (61). Interestingly, in the last years several works have suggested the possibility that organs-in particular the liver-could be induced in accepting tumor cells through secreted factors released by primary tumor, such as inhibitor of metalloproteinases or exosomes (so called "premetastastic niches") (62,63).…”
Section: Pdac Evolution: From Pancreatic Gland To Metastasismentioning
confidence: 99%
“…There are preferential sites for metastases from PDAC, such as liver, lungs, and peritoneum (61). Interestingly, in the last years several works have suggested the possibility that organs-in particular the liver-could be induced in accepting tumor cells through secreted factors released by primary tumor, such as inhibitor of metalloproteinases or exosomes (so called "premetastastic niches") (62,63).…”
Section: Pdac Evolution: From Pancreatic Gland To Metastasismentioning
confidence: 99%
“…It has been reported that ~50% of patients have been confirmed to possess metastasized cancer cells (3). Despite continuous improvements in diagnosis and treatment, this type of cancer is almost invariably fatal, and the 5-year survival rate of patients is ~8% (4,5). PDAC has a high degree of malignant biological characteristics, including invasion and metastasis, which leads to a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Our ability to mimic such dynamic cues (i.e., mechanical forces, hypoxia, and matrix stiffness) on a chip is crucial in modeling cellular events in cancer. For example, epithelial to mesenchymal transition (EMT), a key event in cancer progression and invasion, responds to such dynamic forces in the tumor [28][29][30][31]. The phenotypic transition of the cancerous epithelium into mesenchymal faith enhances their pro-survival tone, migratory capacity, and metastasis [30,32].…”
Section: Organ-on-a-chip (Ooc) Technology In Cancermentioning
confidence: 99%